Halal Certificates And Public Trust: Catalyst Or Challenge For The Indonesian Halal Economy? - Mulia Siregar, Ihsan; Ena Aisyah Simbolon, Siti; Tri Ana Harahap, Choirunnisa; Eni Aisyah Simbolon, Siti; Maharani Nasution, Adinda (Proceedings of International Conference on Islamic Economic Finance and Social Finance (ISSN: XXXX-XXXX) (ESSN: XXXX-XXXX), 2025)
The current phenomenon is that there are several cases of misuse of halal certification. Meanwhile, consumers with higher levels of trust tend to choose halal-certified products. In addition, when consumers do not have enough information about the content, production process, and quality of halal products, they seek trust. Halal product certification is an important solution to this information gap, providing consumers with increased trust in the product. Addressing the phenomenon that occurs, this study aims to describe public trust in halal certification can encourage the growth of the halal economy in Indonesia. This research was conducted with a qualitative approach through literature searches and writings that are closely related to this research problem. Data collection through searches of journal articles from online websites. The results of the study show that halal certification is one of the innovations for businesses, a marketing strategy tool and a competitive advantage that increases business growth.